Oat products digestibility studies and their nutritional information - Piispa, Eija; Alho-Lehto, Pirjo (MTT, 2004)
Carbohydrate containing foods can alter blood glucose and insulin levels in markedly different ways depending on the foods fiber content, particle size and method of preparation. Digestibility can be studied using in vitro or in vivo methods, such as hydrolysis (HI) or glycemic index (GI) measurements (Granfeldt et al. 1992, Jenkins et al. 1981). Recent studies have shown that foods, which have low GI values and maintain normal blood glucose and insulin levels may have metabolic benefits in relation to diabetes and to the reduction of coronary heart disease risk (Jenkins et al. 2002). Glycemic index and digestibility of oat products has been studied mainly on products which have high â-glucan content. These results show beneficial effects of viscous â-glucan on reduction of glucose absoption. Oat products such as oat porridge or oat pasta have not been widely studied. In this study we examined effects of oat pasta and two different oat porridges on glucose absorption using HI and GI methods. Results showed that oat pasta, consisting of oat and wheat flours and oat fibers has low GI value and it is digested slowly. Addition of oat fibers, soluble and insoluble, did not lower GI value. Cooked oat porridge gives medium GI values and the glucose curve maintains in moderate levels long time after porridge has been eaten. Results showed, that digestibility of oat pasta is mostly affected by its structure and digestibility of oat porrigde is affected by its processing or cooking method, fiber and â-glucan content. Granfeldt Y et al. 1992. European Journal of Clinical Nutrition 46:649-60; Jenkins DJ et al. 1981. American Journal of Clinical Nutrition 34:362-366; Jenkins DJ et al. 2002. American Journal of Clinical Nutrition 76:266S-273S.
Keywords: Ka; oat; processing; porridge; pasta; glycemic index; hydrolysis index; digestibility